IMPLANTAÇÃO DE POLÍTICAS P+L NO REUSO DE EFLUENTES INDUSTRIAIS NA PRODUÇÃO DE BIODIESEL - CARVALHO, Núbia Luiza Corrêa; SILVA, Carmem Cícera Maria da; CESCA, Rafaela da Silva; MENDES, Luís Rodrigo Benitez (ANAIS DO ENIC, 2017)
-